RESPON KOMPOSISI MEDIA DAN PANJANG STEK TERHADAP PERTUMBUHAN BIBIT BOUGENVILLE (Bougenvillea glabra L.) - Zuhroh, Mimik Umi; Hartanti, Aprilia; Chak, Saiful (Universitas Panca Marga, 2024)
Bougainvillea Enough popular for lovers plant decoration . Power pull plant bougainvillea there in the sheath flower with pattern color bright And diverse so that Lots interested community​ plant And cultivate it . Bougainvillea plant propagation can be done in two ways, namely generatively and artificially vegetatively. The simplest and easiest artificial vegetative propagation is by stem cuttings. Plant propagation using the cutting system is a plant propagation that produces the same characteristics as its parent. The role of the right planting media will help plants to grow and form callus or potential roots. The composition of the plant media that contains sufficient nutrients and has high porosity is a suitable condition for this cutting system propagation. The purpose of this study was to: 1). determine the effect of planting media composition on the growth of bougainvillea plant cuttings; 2). Determine the effect of cutting length on the growth of bougainvillea seedlings; 3). Determine the interaction that occurs between the composition of the planting media and the length of the cuttings on the growth of bougainvillea seedlings. The experimental design methodology used a Complete Randomized Block Design factorial with factor 1 being the composition of the planting media consisting of 3 levels, namely K0 (soil); K1 (soil: compost = 1: 1); K2 (soil: compost: rice husk charcoal = 1: 1: 1). The second factor is P1 (cutting length 15 cm), P2 (cutting length 20 cm), P3 (cutting length 25 cm), P4 (cutting length 30 cm). The results of the study showed that the composition of the planting media had a significant effect on the parameters of shoot growth days, number and length of shoots, number of leaves and roots, root length and percentage of finished seedlings. The length of the cutting had a significant effect on the day of shoot emergence, number of shoots, number of leaves and roots and root length. The interaction showed a positive effect on the day of shoot emergence, number of leaves, root length and percentage of finished seedlings. Keywords: composition of the planting media, cuttings, Bougainville